2017
DOI: 10.1155/2017/9571470
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Facial Proportions and Their Association with Thumbprint Patterns among Hausa Ethnic Group

Abstract: Background. Evolutionary forces such as founder effect resulted in reproductive isolation and reduced genetic diversity may have led to ethnic variation in the facial appearance and other features like fingerprints pattern. Aim. To determine the pattern of facial proportion based on neoclassical facial canon. The associations between facial proportions and thumbprint patterns were also investigated. Subject and Methods. A total of 534 subjects of 18-25 years of age participated. Direct sensing and photographs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Some genes that were reported in low to medium levels in the skin were found to play a key role in the determination of facial features [31,32]. Some level of association was also documented between thumbprint patterns and facial proportions [4]. These explain the possible linear correlations observed in this study.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Some genes that were reported in low to medium levels in the skin were found to play a key role in the determination of facial features [31,32]. Some level of association was also documented between thumbprint patterns and facial proportions [4]. These explain the possible linear correlations observed in this study.…”
Section: Discussionsupporting
confidence: 70%
“…Therefore, it was suggested that the two traits (fingerprint and facial features) may share the same intrinsic factor that controls them, leading to some significant degree of correlation between the two variables [4]. In previous studies, the features of both fingerprint patterns and facial morphology were reported to be strongly influenced by genetic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have recently been undertaken on fingerprints from the Hausas of Nigeria. Recent studies by Adamu et al (2016aAdamu et al ( , 2016bAdamu et al ( , 2017aAdamu et al ( , 2017b, Adamu (2017), and Adamu and Taura (2017) have investigated the minutiae in the Hausa population in Kano and estimated its association with sexual dimorphism in epidermal ridges, sex variation in thumb minutiae, estimation of body mass index, and sex estimation.. There is therefore a need to assess the type and frequencies of different fingerprint minutiae in Nigerians of other ethnic origins, including Igbo and Yoruba.…”
Section: Introductionmentioning
confidence: 99%
“…F ace and the fingerprint are among the biological features that determine the uniqueness of an individual. 1 Although beauty is subjective, the neo-classical canons have been used as a basis for defining a beautiful face from antiquity to modern days. 2 This has been useful to clinicians in the description, diagnosis, and surgical treatment of abnormal skeletal and facial patterns.…”
mentioning
confidence: 99%